Developing livable cities: do we have what it takes?. Issue 3 (1st September 2020) - Yang, Samuel; Eyler, Amy; Brownson, Ross; Samuels, Linda; Kyung, Grace; Reis, Rodrigo
ABSTRACT: A popular and intuitive way to capture the quality of life in cities is by evaluating 'livability.' This study aims to gain insight on the types, importance, and availability of skills needed to develop livable cities, as perceived by researchers and practitioners. Participants in a separate concept mapping project were asked to provide a list of the skills they found most important to the development of livable cities. Responses were synthesized into broader categories. Survey respondents most referenced Collaboration, Communication, and Community Engagement. In a second phase, respondents were asked to select those that they felt were most important. Collaboration and Community Engagement were the two most frequently selected skills in the second phase. Results were compared against competency requirements for program accreditation in the fields of Public Health, Urban Planning, Architecture, Landscape Architecture, and Parks and Recreation Administration. All are vital partners in livable city development. Further trends, similarities, and differences are discussed. This study underscores the enduring need for 'soft skills, ' non-traditional approaches to education and workforce development, and the increasing relevance of team science. Understanding the skills needed for livable city development helps ensure researchers and practitioners are equipped to participate.